Diabetic Nephropathy Induced by Increased Ace Gene Dosage Is Associated with High Renal Levels of Angiotensin (1–7) and Bradykinin - Nádia Bertoncello; Roseli Peres Moreira; Danielle Yuri Arita; Danielle S. Aragão; Ingrid Kazue Mizuno Watanabe; Patricia S. Dantas; Ralmony Santos; Rodolfo Mattar-Rosa; Rodrigo Yokota; Tatiana Sousa Cunha; Dulce Elena Casarini (Journal of Diabetes Research)
Population studies have shown an association between diabetic nephropathy (DN) and insertion/deletion (I/D) polymorphism of the angiotensin-converting enzyme (ACE) gene (ACE in humans, Ace in mice). The aim was to evaluate the modulation of Ace copies number and diabetes mellitus (DM) on renal RAS and correlate it with indicators of kidney function. Increased number of copies of the Ace gene, associated with DM, induces renal dysfunction. The susceptibility to the development of DN in 3 copies of animals is associated with an imbalance in activity of RAS enzymes leading to increased synthesis of Ang II and Ang-(1–7). Increased concentration of renal Ang-(1–7) appears to potentiate the deleterious effects triggered by Ang II on kidney structure and function. Results also show increased bradykinin concentration in 3 copies diabetic group. Taken together, results indicate that the deleterious effects described in 3 copies diabetic group are, at least in part, due to a combination of factors not usually described in the literature. Thus, the data presented here show up innovative and contribute to understanding the complex mechanisms involved in the development of DN, in order to optimize the treatment of patients with this complication.